A Pilot Trial of Stepwise Implementation of Virtual Reality Mindfulness and Accelerated Transcranial Magnetic Stimulation Treatments for Dysphoria in Neuropsychiatric Disorders - Senda, Megan C.; Johnson, Kevin A.; Taylor, Isabelle M.; Jensen, Mariah M.; Hou, Yang; Kozel, F. Andrew (Depression and Anxiety, 2023)
Dysphoria is a transdiagnostic symptom that causes considerable suffering. Implementation of established self-care and clinical treatment options, such as mindfulness and transcranial magnetic stimulation (TMS), is typically disjointed for conditions involving dysphoria. There is a need for a rapid progression of accessible treatments that can be efficacious across multiple comorbidities. In a pilot stepwise implementation study to assess feasibility and effectiveness, adult participants with dysphoria (depression, anxiety, PTSD, and/or chronic pain) went through a treatment course of VR mindfulness, then accelerated TMS (accel-TMS) over the left dorsolateral prefrontal cortex (left dlPFC), then accel-TMS over the dorsomedial prefrontal cortex (dmPFC). Participants who did not benefit from one treatment phase progressed to the next until remission or study completion. Twenty-four participants were enrolled with 23 in VR mindfulness (phase 1), 19 in accel-TMS left dlPFC (phase 2A), and 13 in accel-TMS dmPFC (phase 2B). For our primary outcome measure of the short form-36 emotional well-being subscale (paired t-test), no significant change was found in phase 1 (n=19, p=.226), significant improvement was found in phase 2A (n=19, p=.038), and no significant change was found in the smaller sample of phase 2B (n=12, p=.089). Symptom improvement was largely supported by clinician-administered scales, with more significant changes found in accel-TMS left dlPFC and dmPFC. The benefits of VR mindfulness were limited; however, both accel-TMS phases showed a significant impact on secondary measures of depression, anxiety, and PTSD. This stepwise protocol shows promise in providing an approach to rapidly improve symptoms of dysphoria in transdiagnostic populations. This trial is registered with NCT05061745.